Mutations in MAP3K7 that alter the activity of the TAK1 signaling complex cause frontometaphyseal dysplasia. - Wade, E; Daniel, P; Jenkins, Z; McInerney-Leo, A; Morgan, T; Addor, M; Ades, L; Bertola, D; Bohring, A; Carter, E; Cho, T; Duba, H; et al. (Elsevier, 2016)
Frontometaphyseal dysplasia (FMD) is a progressive, sclerosing skeletal dysplasia affecting the long bones and skull. The cause of FMD in some individuals is gain-of-function mutations in FLNA, although how these mutations result in a hyperostotic phenotype remains unknown. Approximately one half of individuals with FMD have no identified mutation in FLNA and are phenotypically very similar to individuals with FLNA mutations except for an increased tendency to form keloid scars. Using whole exome sequencing and targeted Sanger sequencing in 19 FMD individuals with no identifiable FLNA mutation, we identified mutations in two genes - MAP3K7, encoding transforming growth factor β (TGFβ)-activated kinase (TAK1) and TAB2, encoding TAK1-associated binding protein 2 (TAB2). Four mutations were found in MAP3K7, including one highly recurrent (n=15) de novo mutation (c.1454C>T, p.Pro485Leu) proximal to the coiled-coil domain of TAK1, and three missense mutations affecting the kinase domain (c.208G>C, p.Glu70Gln; c.299T>A, p.Val100Glu and c.502G>C, p.Gly168Arg). Notably these latter three subjects had a milder FMD phenotype. A further de novo mutation was found in TAB2 (c.1705G>A, p.Glu569Lys). The recurrent mutation does not destabilize TAK1, or impair its ability to homodimerise or bind TAB2, but it does increase TAK1 autophosphorylation and alters the activity of more than one signalling pathway regulated by the TAK1 kinase complex. These findings show that dysregulation of the TAK1 complex produces a close phenocopy of FMD caused by FLNA mutations. Furthermore they suggest that the pathogenesis of some of the filaminopathies caused by FLNA mutations may be mediated by misregulation of signalling co-ordinated through the TAK1 signalling complex.